Building contract claims - Chappell, David; Wiley InterScience (Online service) (Oxford : Wiley-Blackwell, 2011)
Many building projects are the subject of claims - the assertion of a right, usually by the contractor, to an extension of the contract period or an additional payment under the terms of the building contract. Many of these claims are unsound or ill-founded, often because the basic principles are misunderstood. This highly regarded book examines the legal basis of claims for extensions of time and additional payment, and what can and cannot be claimed under the main forms of contract. It includes chapters dealing with direct loss and expense, liquidated damages, extension of time, concurrency.
Introduction -- Time -- Liquidated damages -- Basis for common law claims -- Direct loss and/or expense -- Points of principle -- Potential heads of claim -- Causation -- Global claims -- Preparation and substantiation of claims -- Extension of time under JCT standard form contracts -- Liquidated damages under JCT standard form contracts -- Loss and/or expense under JCT standard form contracts -- Variations -- Claims under GC/Works/1 -- Claims under ACA 3 -- Claims under PPC2000 -- Claims under NEC 3 -- Sub-contract claims.
Previous edition: published as by David Chappell, Vincent Powell-Smith & John Sims. 2005.
Includes index.
Formerly CIP.
Includes bibliographical references and index.
Print version record.
Keywords: Construction contracts -- Great Britain; Breach of contract -- Great Britain; Actions and defenses -- Great Britain; Damages -- Great Britain; LAW -- Military; Actions and defenses; Breach of contract; Construction contracts; Damages; Great Britain; Electronic books